Financial incentives often fail to reconcile agricultural productivity and pro-conservation behavior - Bell, Andrew R.; Rakotonarivo, O. Sarobidy; Bhargava, Apurva; Duthie, A. Bradley; Zhang, Wei; Sargent, Rebecca; Lewis, Amy R.; Kipchumba, Adams (Springer, 2023)
Paying resource users to preserve features of their environment could in theory better align production and conservation goals. We show, however, that across a range of conservation dilemmas, they might not. We conduct a synthesis of dynamic games experiments built around collective action dilemmas in conservation, played across Europe, Africa, and Asia. We find, across this range of dilemmas, that while payments can encourage pro-conservation behavior, they often fail to capitalize on the potential for jointly improving productive and environmental outcomes, highlighting the more nuanced challenge of reconciling livelihoods with conservation goals. We further find production (yield) and the joint production-environment product (i.e., a measure of agricultural production multiplied by a measure of pro-conservation practice) are better preserved in groups that are more educated, more gender diverse and that better represent women. We discuss how the design of incentive programs can better align livelihood and environment goals.